PERTUMBUHAN DAN PRODUKSI BAWANG MERAH DENGAN PEMBERIAN BERBAGAI PUPUK ORGANIK - Fitri Anisyah; Rosita Sipayung; Chairani Hanum (Jurnal Agroekoteknologi, 2014)
ABSTRACTGrowth and Yield of Shallot (Allium ascalonicum L.) with Application of the some of organicfertilizer. Application of in organic chemical fertilizers continuously without organic fertilizers hascaused soil degradation. One of the negative effect is decrease agriculture production such as shallotyield. A solution to solve this problem is to substitute chemical fertilizers application with organicfertilizer that can demage the soil into organik fertilizer. The objective of this research was to studygrowth and yield of shallot with application of organic fertilizer. The research was conducted inPasar 1 Tanjung Sari, from June until August 2012. The research using Randomized Block Designone factor with six compost, were without organic fertilizer (control), compost of empty fruitbuches oil palm, sludge, vermicompost, straw, and municipal solid waste. Parameters were: plantheight, number of plantlet, shoot root ratio, clove dry weight of sample, dry weight of sample andclove number of sample. The results showed that application of organic fertilizer did not hadpositive response to the growth of shallot except for number of plantlet on 3 weeks after plantingtime and shallot dry weight per sample.Key words : palm empty fruit bunches (PEFB), sludge, vermicompost, straw compost, municipalsolid wastecompost, Shallot